Development of a Z39.50 server prototype for the University of the Philippines Library System - Gamara, Ivan Cedric B. (2009)
A Z39.50 server prototype has been successfully developed for the University of the Philippines Diliman library system. The prototype currently can import bibliographic records in MARC format from the UP iLib system. It then indexes the records using an existing technology called Zebra. The records are made available through a web service in which a Z39.50 client software can connect to.